Malware Detection Using Neural Network - Kayum, Syed Irfan; Hossain, Humaira; Tasnim, Naﬁsa; Paul, Arja; Rohan, Alim Aldin (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.